2015
DOI: 10.1021/acs.macromol.5b01469
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure and Work of Adhesion of Poly(n-butyl acrylate) and Poly(n-butyl acrylate-co-acrylic acid) on α-Quartz, α-Ferric Oxide, and α-Ferrite from Detailed Molecular Dynamics Simulations

Abstract: Molecular dynamics simulations are performed for two model pressure-sensitive adhesive (PSA) materials, atactic poly(n-butyl acrylate) [poly(n-BA)] and atactic poly(nbutyl acrylate-co-acrylic acid) [poly(n-BA-co-AA)] at a very low concentration in acrylic acid (one acrylic acid monomer per fifty butyl acrylate monomers plus three acrylic acids at each one of the two chain ends) in the bulk and confined between three crystalline substrates, silica (SiO 2 ) represented as α-quartz, α-ferric oxide (α-Fe 2 O 3 ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 33 publications
5
30
0
Order By: Relevance
“…For less favorable interactions, these peaks would be reduced significantly. Such observations have been shown before for the interfacial systems of acrylic chains on α-quartz, α-Fe 2 O 3 , and α-ferrite where the strong adsorption of acrylic chains on α-quartz and α-Fe 2 O 3 was evidenced by the higher intensities of the local mass density peaks compared with the less pronounced peaks for α-ferrite [26]. These peaks are, on the other hand, influenced by the available space on the surfaces.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…For less favorable interactions, these peaks would be reduced significantly. Such observations have been shown before for the interfacial systems of acrylic chains on α-quartz, α-Fe 2 O 3 , and α-ferrite where the strong adsorption of acrylic chains on α-quartz and α-Fe 2 O 3 was evidenced by the higher intensities of the local mass density peaks compared with the less pronounced peaks for α-ferrite [26]. These peaks are, on the other hand, influenced by the available space on the surfaces.…”
Section: Resultssupporting
confidence: 77%
“…Figure 3 displays the mass density profile, ρ, across the film thickness. Due to the symmetry of the density profiles with respect to the film midplane, one can conclude that the number of polymer configurations embedded in the film thickness was sufficient to provide adequate predictions of the relevant properties studied here [26]. Near the substrates, the density profile shows a profound peak at a distance equal to ~4 Å away from the solid surface.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Many systems of biophysical and technological interest consist of nanoparticles and polymer chains in a confined volume, where not only interactions between polymers and particles but also the volume limitations need to be taken into considerations [ 51 , 78 , 79 , 80 ]. One key study [ 68 ] relating confinement to diblock copolymer nanocomposite is that reported by Lee et al, where they prepared blends of AB diblocks and nanoparticles that are confined between two hard walls separated by a distence using SCFT/DFT calculations.…”
Section: Entropy-induced Transition By External Conditionsmentioning
confidence: 99%
“…For example, the importance of the relationship between dispersion and orientation of graphene nanoribbon and electrical properties has been highlighted by the research group of Sundarara [ 17 , 18 ], and was supported by DPD simulations [ 75 , 76 , 77 ]. Confinement effects in highly-filled polymer composites and nanocomposites are also an important field where energy/entropy considerations play a key role in determining the final structures and properties [ 78 , 79 , 80 ]. For instance, the interactions and conformational characteristics of confined molten polypropylene (PP) chains between ferric oxide (Fe 2 O 3 ) substrates were investigated by molecular dynamics (MD) simulations, showing the influence of the confinement on the buildup imbalance of normal and tangential pressures [ 78 ].…”
Section: Entropy-induced Transition By External Conditionsmentioning
confidence: 99%